Antropología social de las sociedades complejas / Eric R. Wolf, Burton Benedict, J. Clyde Mitchell, Joe Loudon, adrian C. Mayer y Ronald Frankenberg ; compilación de Michael Banton; versión Española de Joaquina Aguilar - Wolf, Eric R.Banton, Michael (1926-) Aguilar, Joaquina (Alianza universidad; 259)
Bibliografía: p. 159-162